"Happy Together": Effects of Brand Community Engagement on Customer Happiness. Issue 1 (2nd January 2019) - Niedermeier, Anna; Albrecht, Lisa; Jahn, Benedikt
Abstract: Because the pursuit of happiness is fundamental, humans perform a wide range of activities, including consumption, to lead a happy life. For marketers, findings from positive psychology suggest that customer happiness may arise through customer engagement. This article proposes a conceptual framework of customer happiness in brand communities and analyzes the effect of customer engagement on customer happiness, as well as on the ultimate outcomes of word of mouth and purchase intentions. Structural equation modeling provides a test of the model through an empirical study with 518 members from the online brand community for a German automotive brand. Customer engagement exerts a significant positive effect on customer happiness, which in turn increases positive word of mouth and purchase intentions. Therefore, marketing managers should invest in brand communities to engage customers and build and maintain their happiness and loyalty.